Gestational zearalenone causes fetal intrauterine growth restriction partially through deriving ROS-Drp1 mediated placental PANoptosis - Jie Ru Liu; Fang Nan Wu; Shuai Lin; Chen Chen; Yan Liu; Jing Wen Fan; Qiang Hong; Yuan Hua Chen (Ecotoxicology and Environmental Safety)
The ubiquity of zearalenone (ZEA) in cereal-based products and the aquatic environment raises growing concerns about health problems to humans and animals. Here, we explored the mechanism by which ZEA exposure during pregnancy induced fetal growth restriction (FGR). Interestingly, both fetal weights and crown-rump length were significant decreases when dams were administrated with ZEA. Consistently, the incidence of FGR is significantly increased in ZEA group in a dose-dependent manner. Moreover, mean placental weight and diameter was significantly reduced in ZEA group, suggesting that poor placental development may be involved in ZEA-induced FGR. The genome-wide expression profiles of mouse placentas were significantly different between two groups by RNA-sequencing. GO and KEGG analysis indicated significant enrichment of these differentially expressed genes in mitochondrial apoptotic signaling pathway, inflammatory cell apoptotic process, necroptosis, and regulation of mitochondrial membrane potential. Further study showed that mitochondrial quality control disorder and PANoptosis plays an important role in ZEA-induced poor placental development. Mdivi-1, an inhibitor of Drp-1, attenuated ZEA-induced mitochondrial quality control disorder and PANoptosis in mouse placentas and human placental trophoblasts. N-acetylcysteine (NAC), an antioxidant, abolished ZEA-induced mitochondrial quality control disorder and PANoptosis in mouse placentas and human placental trophoblasts. Importantly, Mdivi-1 and NAC rescued gestational ZEA exposure-induced poor placental development and FGR in mice. Our results indicate that ZEA exposure during pregnancy caused poor placental development and subsequently FGR may be via deriving ROS-Drp1 mediated placental PANoptosis.